IMPLEMENTASI KEPEMIMPINAN TRANSFORMASIONAL TERHADAP PENERAPAN GERAKAN 7 KEBIASAAN ANAK INDONESIA HEBAT - Suherman, Maman; Subandi, Muhammad; Sukmawati Kusnadi, Fitria; Saofanita, Saofanita; Khoiriyah, Nikmatul (Penerbit Lafadz Jaya, 2025)
The degradation of student character in today's era of globalization poses a significant challenge for the education sector. Students are not only expected to be academically competent but also to possess strong character, responsibility, independence, and positive social behavior. In this context, transformational leadership is seen as an effective strategic approach to foster a school culture that supports character education. One such program used as a tool for character development is the “7 Habits of Great Indonesian Children Movement,” which contextualizes universal values into Indonesian cultural and religious frameworks. This study aims to explore the implementation of transformational leadership in supporting the 7 Habits program at SMP Negeri 1 Bojongsoang. Employing a qualitative approach with a case study method, data were collected through interviews, observations, and document analysis involving the school principal, teachers, and students. The research focuses on the forms of transformational leadership implementation, its impact on the program, and the supporting and inhibiting factors affecting its execution. The findings reveal that the school principal’s transformational leadership was effective in fostering a positive shift in school culture. Through exemplary behavior, inspirational motivation, teacher empowerment, and systematic supervision, the principal successfully facilitated the internalization of positive habits in students’ daily lives.